Apocalypse... Now? Molecular epidemiology, predictive genetic tests, and social communication of genetic contents - Luis David Castiel
The author analyzes the underlying theoretical aspects in the construction of the molecular watershed of epidemiology and the concept of genetic risk, focusing on issues raised by contemporary reality: new technologies, globalization, proliferation of communications strategies, and the dilution of identity matrices. He discusses problems pertaining to the establishment of such new interdisciplinary fields as molecular epidemiology and molecular genetics. Finally, he analyzes the repercussions of the social communication of genetic content, especially as related to predictive genetic tests and cloning of animals, based on triumphal, deterministic metaphors sustaining beliefs relating to the existence and supremacy of concepts such as 'purity', 'essence', and 'unification' of rational, integrated 'I's/egos'.